2016
DOI: 10.14429/djlit.36.5.10174
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Tools in Library Service Delivery: The Case of Academic Libraries in South-East Zone of Nigeria

Abstract: A lot of literature exists concerning acceptance and utilisation of 'social networking' (SN) tools in academic libraries from different parts of the world. However, only a handful of work has been done on librarians' use of SN in academic libraries in South-East, Nigeria. Therefore, this study tends to investigate librarians' use of SN in academic libraries in South-East, Nigeria. This study adopted a survey design using 173 librarians from the zone. Finding showed that some librarians used SN in libraries for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This goes far to establishing a cordial relationship among librarians and as well their patrons. Therefore, Omeluzor et al (2016) suggested that academic libraries prioritise training and retraining of librarians in the emerging digital era. The literature revealed that academic librarians acquire the skills for the use of Web 2.0 tools through self-practice, friends/colleagues and attendance at workshops (Adeleke and Habila, 2012; Baro et al, 2013; Daluba and Maxwell, 2013; Fasola et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This goes far to establishing a cordial relationship among librarians and as well their patrons. Therefore, Omeluzor et al (2016) suggested that academic libraries prioritise training and retraining of librarians in the emerging digital era. The literature revealed that academic librarians acquire the skills for the use of Web 2.0 tools through self-practice, friends/colleagues and attendance at workshops (Adeleke and Habila, 2012; Baro et al, 2013; Daluba and Maxwell, 2013; Fasola et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Using social media to understand library values and missions and learn about concerns in using the library. forums.techsoup.org (2019) and Omeluzor et al (2016) helps the library to advertise and follow latest library development and can also be helpful to provide reference and information services. This will help to create a platform to engage library users to get connected to the library services.…”
Section: Review Of Social Media Marketing and Librariesmentioning
confidence: 99%